2017
DOI: 10.1080/1350293x.2018.1412050
|View full text |Cite
|
Sign up to set email alerts
|

Is cognitive development at three years of age associated with ECEC quality in Norway?

Abstract: In countries with universal access to early childhood education and care (ECEC), child participation is high across a range of socioeconomic groups. However, ECEC quality is often varying, and many children spend much time in ECEC settings that are not necessarily high quality. In this observational study, we therefore examined the relationship between observed ECEC quality and children's cognitive development at age three years in Norway-a country that provides universal access to ECEC from age one. The sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 27 publications
1
12
1
1
Order By: Relevance
“…Notably, the narrow between-class standard deviations in ITERS-R score also indicate that few centers excel in general language stimulation. A study using the same data did not find any association between ITERS-R score and cognitive skills in 3-year-olds (Eliassen et al, 2018). Although these studies were of younger children than those in our study, this may indicate that children in Norwegian ECEC centers experience somewhat limited general academic stimulation apart from what takes place in the preschool activities.…”
Section: Pre-academic Activities -A Potential Boost For Somecontrasting
confidence: 71%
See 1 more Smart Citation
“…Notably, the narrow between-class standard deviations in ITERS-R score also indicate that few centers excel in general language stimulation. A study using the same data did not find any association between ITERS-R score and cognitive skills in 3-year-olds (Eliassen et al, 2018). Although these studies were of younger children than those in our study, this may indicate that children in Norwegian ECEC centers experience somewhat limited general academic stimulation apart from what takes place in the preschool activities.…”
Section: Pre-academic Activities -A Potential Boost For Somecontrasting
confidence: 71%
“…While there exists socio-demographic selection into early ECEC in Norway as well (Sibley, Dearing, Toppelberg, Mykletun, & Zachrisson, 2015;Zachrisson, Janson, & Naerde, 2013), it does not seem to be systematic selection into the process-and instructional quality of the centers (Eliassen, Zachrisson, & Melhuish, 2018). Given the relatively homogenous structural quality across centers (Winsvold & Guldbrandsen, 2009), it is unlikely that there should be strong selection into centers with a particularly focus on pre-academic activities.…”
Section: The Case Of Norwaymentioning
confidence: 99%
“…Two other studies from the BePro project have also used the ITERS-R. In the first one, Eliassen et al (2018) used the total ITERS-R score to investigate associations between ECEC quality and children's cognitive development. Their results showed no concurrent associations between children's cognitive development and ECEC quality.…”
Section: Structural Factors Related To Interaction Quality In Ececmentioning
confidence: 99%
“…Overall, the literature suggests that staff in home-based settings for children under age 3, in comparison to staff working in centre-based settings, is less likely to have higher educational qualifications and specialised training in early childhood (Bigras et al, 2010 [89]; Eckhardt and Egert, 2018 [4]; Groeneveld et al, 2010 [90]; OECD, 2018 [1]). Home-based providers are also more likely to have less access to resources and supports and fewer opportunities for professional development than centre-based staff (OECD, 2018 [1]; Tonyan, 2017 [91]).…”
Section: Home-based Ecec Associated With Less Regulation and Poorer Qmentioning
confidence: 99%
“…A more recent study, conducted in Germany, found that the proportion of dual language infants and toddlers in groups was significantly lower in home-based provision when compared to infant/toddler centres (Eckhardt and Egert, 2018 [4]). One possible explanation might hinge on specific implemented policies that directly aim at increasing disadvantaged families' participation in ECEC centres.…”
Section: Unclear If Centre Vs Home-based Care Divide Is Attached To mentioning
confidence: 99%